Analisis Potensi Air Tanah Dengan Geolistrik Sebagai Alternatif Sumber Air Irigasi Pada Desa Bagetango, Kecamatan Lopok, Kabupaten Sumbawa Besar: Analysis Groundwater Potential Using Geoelectric As Alternative Water Irrigation In Bagetango Village, Lombok Regency Sumbawa Besar - Asid, Nurul Jannah; Balafif, Sabri (Media Ilmiah Teknik Sipil, 2024)
Climate conditions affect the water balance in an area. Bange Tango Regency is an area that is dominant with agricultural land, so it requires good irrigation to develop the potential of agricultural land, however meeting agricultural irrigation water needs is still difficult, especially entering the peak dry season in early August to mid-late October with average temperatures. -The highest average is above 32°C, even in October, with an average lowest temperature of 33°C with a low water vapor concentration even though it is influenced by the southeast wind which blows from the Australian Continent towards the Asian Continent which passes through the Sumbawa Island area and its surroundings. . This research was carried out to detect new water sources apart from the use of surface water sources such as river dam water, lakes and shallow wells (dig wells) in the context of land extensification to increase the usability of agricultural land in the dry season. This research is experimental for the detection of groundwater potential using the Schlumberger configuration resistivity geoelectric method with two sounding point distances of 200 m. The research results show that the aquifer layer in this area is sandstone with a resistivity value of 26.15 Ωm and at a depth of 48.56 to a depth of 54.77 MBMT, while the estimated optimum pumping discharge is ± 1.00 liters/second.